Purificación y cuantificación de glicerina cruda y adaptación del método ASTM D6584 para la determinación de glicerina en biodiesel - Robles Chaves, Diana (2014)
In this paper an analytical method is validated for the purification and quantification of the content of glycerol in samples of crude oil from the production of biodiesel fuel. We compared the purity of the glycerol present in the crude oil directly with the purity obtained after purification. The analytical parameters evaluated were precision and recovery. We validated also the method to determine the free and total glycerol in samples of biodiesel fuel with a gas chromatograph according to standard ASTM D6584. The linear working areas, the detection and quantitation limits, the sensitivity of calibration and the precision in terms of repeatability were determined for glycerol, monoolein, diolein and triolein, and the accuracy for glycerol. Biodiesel fuel in two batches was analyzed; the content of glycerol in both batches exceeded the fraction of total glycerol allowed according to a Central American Technical Regulation, and one batch exceeded the fraction of free glycerol.